Estudio de prefactibilidad para la implementación de una planta productora de chupetín orgánico relleno de goma de mascar biodegradable - Galán Loza, Angel Aaron (2021)
The population at present is opting for a better care of their body, either by exercising, consuming different supplements such as vitamins, minerals, etc., and also as an important point by having a good diet. But it is also known that today the levels of stress and nervousness are higher, which is why a large part of the population uses the consumption of confectionery foods as a method of calm or relaxation. (Scientific American, 2015) That is why the decision was made to develop a pre-feasibility project for an organic lollipop production plant which is based on the implementation of a totally natural lollipop made with panela, fruit juice flavors, natural colorants and which contains as a filling. a biodegradable chewing gum. In turn, the lollipop will be packaged with a biodegradable plastic wrap and their respective sales boxes will provide care for the environment. In this project, the procedure of the production process of the organic lollipop and the machines that allows its production will be shown, the respective demand for the project will be calculated, it will be demonstrated what the capacity of the plant will be and the necessary investments that are carried out. This new contribution to society will be made through this new product that will serve to further increase healthy consumption and in turn promote all the benefits that it can provide us.